Fresno County Courthouse Park: Courthouse, Statues and Sculptures - Watkins, Howard::::::::: (1989)
Bust of Seated Dr. Chester Rowell facing the Rowell Building (Tulare and Van Ness); city's 1st skyscraper Fresno Mayor 1909-1912 when he died